2003
DOI: 10.1046/j.1365-2036.2003.01451.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, comparative study of the para‐aminobenzoic acid test and faecal elastase 1 in the assessment of exocrine pancreatic function

Abstract: SUMMARYBackground: The assessment of exocrine pancreatic insufficiency is part of the routine work-up of patients with persistent diarrhoea or suspected steatorrhoea. Direct and indirect tests for the diagnosis of exocrine pancreatic insufficiency have their drawbacks. Measurement of faecal elastase 1 by enzyme-linked immunoabsorbent assay is a simple, non-invasive, robust test for exocrine pancreatic insufficiency. Methods: We performed a prospective comparison of the para-aminobenzoic acid test and faecal el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…FE-1 is well documented in quantitative studies to be stable during intestinal transit and studies demonstrate significant correlation between fecal elastase and levels of other pancreatic enzymes such as duodenal lipase, amylase, trypsin, and bicarbonate concentration [2][3][4][5][6]. Fecal elastase is concentrated in human feces compared with pancreatic juice and is a simple, non-invasive and inexpensive test [2,7,8]. As a result, FE-1 has replaced ''tube tests'' and fecal fat measurement in most centers and has become the sole arbiter of pancreatic insufficiency for many.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…FE-1 is well documented in quantitative studies to be stable during intestinal transit and studies demonstrate significant correlation between fecal elastase and levels of other pancreatic enzymes such as duodenal lipase, amylase, trypsin, and bicarbonate concentration [2][3][4][5][6]. Fecal elastase is concentrated in human feces compared with pancreatic juice and is a simple, non-invasive and inexpensive test [2,7,8]. As a result, FE-1 has replaced ''tube tests'' and fecal fat measurement in most centers and has become the sole arbiter of pancreatic insufficiency for many.…”
mentioning
confidence: 99%
“…Pancreatic disease is diagnosed on a combination of clinical history, abnormal pancreatic function tests, and radiological criteria [8]. Although subtle changes in exocrine function can be identified in patients with early pancreatic disease, overt steatorrhea does not occur until approximately 90% of the glandular function has been lost [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Glasbrenner et al [26] concluded that the FE-1 is comparable to the standard serum PLT in the diagnosis of pancreatic insuffi ciency. A recent comparative study by Sonwalkar et al [27] has concluded that the FE-1 has a superior diagnostic performance to the NBT-PABA test. The NBT-PABA and PLT have similar sensitivity and specifi city when compared to invasive tube tests [2] , but the NBT-PABA is now rarely used in the UK as pharmaceutical grade reagents are not available.…”
Section: Discussionmentioning
confidence: 99%
“…Various other clinical (Body weight, nutritional status, frequency of bowel movements, stool character, abdominal pain, global disease symptom score, quality of life score) as well as laboratory indicators (fecal elastase, fecal chymotrypsin, etc) may be used to test adequacy of PES in various studies. Of the laboratory tests, fecal elastase is a useful non-invasive test for detection of PEI, [110][111][112] but its usefulness in evaluating treatment compliance with PES has not been described.…”
Section: Dovepressmentioning
confidence: 99%